Transition of the Russian federation to new educational standard: independent work of students as a factor in the quality of educational process* - Kremlev Artem; Bazylev Dmitry; Margun Alexey; Zimenko Konstantin (SHS Web of Conferences, 2016)
The paper is devoted to changes in the organization of independent work of students. These changes are associated with transition of the Russian Federation to new educational standards. In this regard, systemically-active approach to educational process, which is also called competence-based approach, comes to replace the knowledge-based model of education. Independent work of students as one of the main components of the competence-based approach is aimed not only at achieving of educational goals, but mainly on the formation of personal qualities of the future specialist - self-knowledge, self-development and self-realization. These qualities form a new competent person who meets the requirements of the labor market. The research includes consideration of issues such as organization, planning, monitoring methods of self-dependent student work taking into account the requirements of the educational standard.